“Medición de la satisfacción de la calidad de servicios en el departamento de inquilinato GAD municipal cantón Quevedo, año 2023”. - Franco Coronel, Ginger Andreina (2023)
The purpose of this research is to identify the quality management in the services offered by the Tenant Department of the Municipal GAD of the Canton of Quevedo, with the interest of evaluating through the SERVQUAL model with the identification of the possible gaps that exist in the quality of the services provided by this department. The methodological approach of this research consisted of a quantitative study that collected information on user satisfaction, quality of services and other relevant factors. The sample of participants included 384 users of the Tenant Department of the Municipal Gad of the Canton of Quevedo. The interview was used to collect information from the public servants of the department, while the surveys were directed towards the users of the service. The questions were evaluated using a 5-point Likert scale, and then the information collected was tabulated and graphically represented in Excel. For the analysis of this study, the corresponding calculations were used in the SPSS V25 statistical software. The results revealed total dissatisfaction on the part of users when it comes to the accessibility of services. This is reflected in aspects such as the appearance of the facilities, the information provided, timely attention, confidence in the service, and individualized attention. Consequently, the findings underscore the imperative need to improve the quality of services offered by the Tenancy Department.